Creative Tourism in Destination Brand Identity (Vallis Aurea, 2023)
This paper analyses the emerging trends in creative tourism, as well as the possibilities of developing creative offer as a means of sustainable development (protection of resources, socio-cultural elements, natural elements and improving the local population’s standard of living) of small historic towns on the Opatija Riviera (Volosko, Kastav, Lovran, Veprinac, Mošćenice, Brseč). It further analyses the current state of creative offer, sets the goals and suggests some possible strategies for developing creative tourism (educational workshops, creative workshops, etc.) as both the basic and additional element of the tourist offer based on sustainable principles, and for creating a recognizable destination brand identity through a valorisation of uniqueness and diversity. The paper also answers the key questions of creative tourism offer enrichment and enhancement, and defines the means to innovate the promotional strategy with the goal of repositioning. The reconception of development in small historic towns and, ultimately, attracting future tourists , requires a synergy of all offer stakeholders, local communities and indigenous residents in forming new elements of creative initiatives through a valorisation of the past and the present.